Interpretasi Hukum “Anak Di Luar Perkawinan” Dalam Undang-Undang Perkawinan 1974 (Studi Pandangan Hakim Pengadilan Agama Provinsi Daerah Istimewa Yogyakarta) - Mahmud Mahmud (UIN Sunan Kalijaga Yogyakarta, 2019)
This research was conducted with the aim to findout what the judge's view of the legal interpretationabout the outside marriage state of children and howthe interpretation of the judge's judgments regardingthe decision of the panel judges related to the outsidemarriage state of children according to the state viewsof the Religious Courts of Yogyakarta Special Province.In this method of study using the Juridical Sociologicalmethod that a combination of fields that use primarydata and secondary data in the form of interviews withinformants and this study is descriptive analytical.Based on the approach method concluded: 1. Accordingto the marriage law Law No. 1 of 1974 in Chapter IX,Article 43 paragraph (1) a child out of wedlock only hasa civil law with his mother and his mother's family. Butwith the decision of the constitutional court No. 46 /PUUVIII / 2010 read: